Biological denitrification and dephosphorisation of a fixed bed reactor packed with long-term carbon release composite under a magnetic field. (4th February 2020) - Tu, Shuchen; Lv, Fengzhu; Meng, Zilin; Zhang, Rui; Zhang, Yihe
A novel multiple-component carbon source mainly with hemp fibre (HF) and biodegradable polybutylenes succinate (PBS) was prepared and filled in two fixed bed bioreactors to remove nitrate nitrogen and phosphorus from simulated groundwater. A 121 days' monitoring indicates that denitrification and dephosphorisation of bacteria are influenced by temperature, but a magnetic field can decrease the influence. With the introduction of a magnetic field, the average nitrogen and phosphorus removal was improved to be 93.18% and 78.68% respectively. Meanwhile the average effluent concentration of chemical oxygen demand (COD) decreased from 51.2 mg·L –1 to 30.8 mg·L –1 . The morphology and the biofilm attaching amount measurement indicated more bacteria were attached onto the composite and more composite was consumed correspondingly. These data displayed a linkage effect for efficient water treatment and a promising long-term carbon-release material.